T cells genetically engineered to overcome death signaling enhance adoptive cancer immunotherapy - Yamamoto, Tori N.; Lee, Ping-Hsien; Vodnala, Suman K.; Gurusamy, Devikala; Kishton, Rigel J.; Yu, Zhiya; Eidizadeh, Arash; Eil, Robert; Fioravanti, Jessica; Gattinoni, Luca; Kochenderfer, James N.; Fry, Terry J.; et al. (Journal of Clinical Investigation, 2019)
Across clinical trials, T cell expansion and persistence following adoptive cell transfer (ACT) have correlated with superior patient outcomes. Herein, we undertook a pan-cancer analysis to identify actionable ligand-receptor pairs capable of compromising T cell durability following ACT. We discovered that FASLG, the gene encoding the apoptosis-inducing ligand FasL, is overexpressed within the majority of human tumor microenvironments (TMEs). Further, we uncovered that Fas, the receptor for FasL, is highly expressed on patient-derived T cells used for clinical ACT. We hypothesized that a cognate Fas-FasL interaction within the TME might limit both T cell persistence and antitumor efficacy. We discovered that genetic engineering of Fas variants impaired in the ability to bind FADD functioned as dominant negative receptors (DNRs), preventing FasL-induced apoptosis in Fas-competent T cells. T cells coengineered with a Fas DNR and either a T cell receptor or chimeric antigen receptor exhibited enhanced persistence following ACT, resulting in superior antitumor efficacy against established solid and hematologic cancers. Despite increased longevity, Fas DNR–engineered T cells did not undergo aberrant expansion or mediate autoimmunity. Thus, T cell–intrinsic disruption of Fas signaling through genetic engineering represents a potentially universal strategy to enhance ACT efficacy across a broad range of human malignancies.
CRIS-Team Scopus Importer:2023-03-23